Object continuity through invisible retinal motion at saccadic speed - Melis Ince; Carolin Hübner; Martin Rolfs (Proceedings of the National Academy of Sciences, 2025)
Saccadic eye movements rapidly shift the visual scene across the retina, raising the question of how object correspondence is established between gaze fixations. Using submillisecond video projection, we isolated the role of high-speed retinal motion from saccade-related extraretinal signals. We introduced high-speed motion in a quartet motion display, a classic tool for studying long-distance object correspondence. While motion visibility dropped to chance level at saccadic speeds, even invisible motion robustly biased object correspondence. These results demonstrate that retinal motion alone can support object continuity across saccadic image shifts.